Responsabilidad social universitaria e imagen institucional en la filial Requena de la Universidad Nacional de la Amazonía Peruana 2023 - Bernuy Rios, Dorian Maria (2024)
The purpose of this final report was to determine the relationship between university social responsibility and institutional image in the Requena Branch of the National University of the Peruvian Amazon, 2023, where the applied method was applied, descriptive-correlational level with a non-experimental design. Opting for a population of 300 students with a sample of 169 to whom a questionnaire was applied to collect information. The results indicate that university social responsibility is regular (36%), this is due to agreements with various organizations that contribute to social development, such as the State, NGOs, international organizations and companies. However, there is a lack of action regarding environmental problems. Although sometimes research focused on sustainable development objectives is encouraged, and the university has communication strategies that show its commitment to social situations in society. For its part, the institutional image is considered regular according to 36% of evaluations, this is because the teaching staff generally complies with the scheduled activities, but sometimes shows faults in their corporate ethics, it has also been found that the infrastructure of the building is sometimes good and that the university can be the most economical option on the market. Finally, it is concluded that there is a significant correlation between the variables, demonstrated by a moderate positive Rho coefficient of 0.424 and that it is highly significant at the 0.000 level.